Clinicopathologic features, comorbid diseases, and prevalence of pulmonary hypertension in dogs with bronchomalacia - Jennifer Gamracy; Kelly Wiggen; Aida Vientós‐Plotts; Carol Reinero (Journal of Veterinary Internal Medicine, 2022)
Abstract Background Reports of clinicopathologic features of bronchomalacia (BM) differ because of inconsistent definitions and frequent prevalence of comorbid cardiopulmonary disease. Pulmonary hypertension (PH) secondary to BM is poorly described. Objectives Dogs with BM will be older but of any somatotype, and increased expiratory effort, ≥1 comorbid disease, and PH will be more common than in dogs without BM. Animals Client‐owned dogs (n = 210) evaluated for respiratory signs. Methods Medical records of dogs with paired inspiratory: expiratory‐breath‐hold computed tomography, tracheobronchoscopy, or both between January 2016 and December 2019 were retrospectively reviewed. Comparisons between dogs with and without BM using Mann‐Whitney rank sum or χ2 tests (P < .05 significant were made). Because of high numbers of variables, criteria with high prevalence (>25%) were identified (n = 10) for univariate analysis (P < .005 significant). Significant variables were submitted for multivariate analysis. Results Bronchomalacia was identified in 41% of dogs of all sizes/somatotypes; 38% were >10 kg. All dogs with BM had ≥1 comorbid cardiopulmonary disorder. Dogs with BM were significantly older (P < .001), smaller (P < .001), and were more likely diagnosed with tracheal or mainstem bronchial collapse (P < .001) or bronchiectasis (P < .001). Multivariate analysis confirmed associations with age, tracheal or mainstem bronchial collapse, and bronchiectasis. In dogs with BM, PH was more prevalent. Conclusions and Clinical Importance Although significantly more common in older, smaller dogs, BM occurs in dogs of all sizes and in all instances with comorbidities. Echocardiography should be considered in dogs with BM to identify PH.